Rappers and biographers: biographical narratives and education for peace with juvenile offenders - Argüello Parra, Andrés; Rojas Cepeda, Sebastián; Cruz Guzmán, Jeidy (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of the article is to analyze experiential narratives within the framework of a didactic proposal for Peace Education named "My autobiography", carried out with a population of the Adolescent Criminal Responsibility System (SRPA) of the Amigoniano Youth Center of Tunja, Boyacá (Colombia). Originality: The research is focused on the principle of human learning historicity, allowing the socio-cultural context analysis and the associated factors that give meaning from biographical art to the life practices of young offenders. Method: a didactic proposal is examined based on the socio-educational approach of life stories as a training practice, which was developed in three methodological phases, with the following strategies: awareness raising, design and production of personal content or autobiographies that were articulated to Rap/Hip Hop style of music, forum cinema and visits by urban artists. Analysis: The production of unpublished texts was structured and recorded as musical narratives emerging categories associated with the contextual and dynamic conditions of life underlying criminal behavior, it allowed to conclude the autobiographical contribution in didactics expressed in the language of music, as a potential to redirect criminal trajectories towards stages of social integration, citizenship and active peace building.